Penerapan Metode SImple Additive Weighting (SAW) Untuk Rekomendasi Prioritas Relationship Marketing Terbaik Berdasarkan Topik Pencapaian Di PT. Bank - Dona Ramadhani; Syafrial Nursaily (TeknoIS : Jurnal Ilmiah Teknologi Informasi dan Sains, 2022)
PT. The Bank is a financial services company engaged in the banking sector, in carrying out operations it selects outstanding employees in each part of its work unit, especially the sales unit. Relationship Marketing is a person who takes an approach in managing corporate relationships with customers at the business level so that they can maximize communication and marketing through managing various different contacts. This research development for the Best Relationship Marketing Priority Recommendation will be recommended to Branch Managers by applying the SAW (Simple Additive Weighting) method and building a prototype with a Web-based system. Using 5 criteria that have been determined by PT. Bank, namely: AVG Performance, Attendance, Teamwork, Responsibility, and Loyalty. The system was tested with 5 RM data as testing data at PT. The bank with the highest-ranking score is RM B with a score of 1.00. The feasibility of the system was tested by the feasibility percentage given to information systems experts and users involved with the results obtained of 98%. The effectiveness of the application of the method was also tested using the Spearman Correlation Rank with the test results obtained at 0.9516